Magmatismo da serra da alegria, grupo amonguijÁ, maciÇo rio apa sudoeste do estado do mato grosso do sul - Godoy, Antonio Misson [UNESP]; Manzano, Jefferson Cassu [UNESP]; De Araújo, Larissa Marques Barbosa; Godoy, Laís Paciência [UNESP] (My University, 2014)
The Paleoproterozoic rocks of the magmatic sequence of Serra da Alegria are inserted in the Apa Massif in the southwest of Mato Grosso do Sul state. Constitute the north segment of Alumiador Batholith and are associated to the Alumiador Plutonic Suite of the Amonguijá Group rocks. In the Serra da Alegria Range occur two differentiated and contemporary magmatic sequences: one with basic-ultrabasic composition and marginal occurrence, and another with acidic-intermediate composition in the central portion. On the west and south portions, the foothills of the escarpment of the sierra, dominate the rocks constituted of magnetite gabbros, quartz gabbros and leuco gabbros, basic pegmatites and anortosites. In the central region dominate reddish rocks with the monzodioritic and monzogranitic composition, inequigranular of middle to fine grained, micro porphyritic locally isotropic and granophyric. The magmatic evolution the Serra da Alegria is possibly represented by an interaction of felsic and mafic magmas involved in magmatic mixing processes, one whith subalkaline composition generated by mantle derivation and associated with intense magmatic segregation processes and, the other, with calcium-alkaline composition of high potassium generated from the melting of lower crustal rocks. They represent sin-collisional rocks of one of the igneous events of Amonguijá Magmatic Arc.
Magmatism saw joy, amonguijÁ, group, mass rio apa southwest state mato grosso do sul
Keywords: Alumiador plutonic suite; Amonguijá group; Lithogeochemistry; Serra da alegria